The Use Of Social Media As A Platform For Presenting English Learning Materials - Alvin Maulana; Hesty Widiastuty; Zaitun Qamariah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This study discusses the benefits of social media as a medium for learning English. This is motivated by the current world of education, where with the rapid advancement of technology in the current era, teachers are always required to take advantage of existing facilities, one of which is social media as a complementary medium for learning material. This study aims to describe the benefits and uses of various social media, which can be used in education. The research method used to write this article is library research. The data collection technique is to collect validated references and then apply them in narrative form. The study results show that social media can greatly benefit the world of education if every teacher in Indonesia makes the most of it.